(untitled) (Journal of Kathmandu Medical College, 2022)
Hospitals and health systems face a new shortage of nursing staff: a lack of experience. As older nurses retire and the influx of new nurses continues to grow, the net effect is a decline in the overall experience of the nursing workforce. At the same time, the provision of health care is becoming increasingly complex; call this phenomenon “the experience-complexity gap.” If not addressed, the gap between experience and complexity will widen and put quality and safety.